Warning traffic sign detection using learning vector quantization & hough transform and recognition based on HOG - Tora, Moumita Roy (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.